Individual Well-Being as predictors of Couple Resilience among Sexually and Gender-Diverse Persons in South Africa and Nigeria - Olaseni, Abayomi O. (Journal of Cultural Analysis and Social Change, 2026)
Sexually and gender-diverse (SGD) people in Africa face enduring structural and psychosocial challenges that may undermine couple resilience. Despite the growth of global research, empirical evidence linking individual well-being to couple resilience among SGD populations remains limited. This study examined whether individual factors predict couple resilience among SGD adults in Nigeria and South Africa, while controlling for socio-demographic characteristics. Using a cross-sectional design, data from 194 SGD individuals (mean age = 31.25, SD = 10.76) were analysed using hierarchical multiple regression. In Model 1, socio-demographic variables explained 17.3% of the variance in couple resilience, [F(6, 85) = 2.97, p < .01], with ethnic/racial background emerging as the only significant predictor (β = .29, p = .006). Model 2 showed that individual well-being significantly predicted couple resilience, [F(1, 74) = 2.04, p < .05], accounting for an additional 14.6% of the variance (ΔR² = .146). Overall, individual well-being significantly predicts couple resilience among SGD populations beyond socio-demographic influences. Limitations include the purposive sampling approach and the use of self-reported measures, which may affect generalisability. Recommendations and implications for practice, policy, and theory are mentioned.